2021
DOI: 10.1542/peds.2020-0815
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D for Growth and Rickets in Stunted Children: A Randomized Trial

Abstract: BACKGROUND AND OBJECTIVES: Vitamin D is essential for healthy development of bones, but little is known about the effects of supplementation in young stunted children. Our objective was to assess the effect of vitamin D supplementation on risk of rickets and linear growth among Afghan children. METHODS:In this double-blind, placebo-controlled trial, 3046 children ages 1 to 11 months from inner-city Kabul were randomly assigned to receive oral vitamin D 3 (100 000 IU) or placebo every 3 months for 18 months. Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…We detected that risk of stunting and underweight did not elevated in low serum vitamin D. In line with our finding, a double-blind, placebo-controlled trial on 3,046 children ages 1-11 months from inner-city Kabul indicated that supplementation with 100,000 IU vitamin D3 for 18 months had no effect on weight age, weight for height, height for age (31). In contrast to our findings, Kumar et al, in a randomized clinical trial, investigated the effects of 35 µg/week vitamin D in low birth weight infants (1.8-2.5 kg) from birth up to 6 months of age in India.…”
Section: Discussionsupporting
confidence: 88%
“…We detected that risk of stunting and underweight did not elevated in low serum vitamin D. In line with our finding, a double-blind, placebo-controlled trial on 3,046 children ages 1-11 months from inner-city Kabul indicated that supplementation with 100,000 IU vitamin D3 for 18 months had no effect on weight age, weight for height, height for age (31). In contrast to our findings, Kumar et al, in a randomized clinical trial, investigated the effects of 35 µg/week vitamin D in low birth weight infants (1.8-2.5 kg) from birth up to 6 months of age in India.…”
Section: Discussionsupporting
confidence: 88%
“…Half were on placebo and half received 100,000 IU of vitamin D every 3 months for 18 months. (46) There was no effect of the bolus vitamin D treatment on growth, and in a subgroup of 20% of children who received radiographic evaluation, rickets frequency was the same (5.4%) between bolus vitamin D and placebo groups. Clearly bolus dosing of vitamin D also contrasts sharply with the historical precedent of daily dosing benefits in the prevention and treatment of rickets.…”
Section: Effects Of Bolus Dosing On Ricketsmentioning
confidence: 81%
“…(43) Other observational studies suggested that hospitalization rates are doubled, and critical care and mortality are tripled in adults with vitamin D deficiency. (30,44,45) Further, Akbar et al (46,47) reviewed 14 studies with almost one million adults in 2021 and concluded that 25(OH)D deficiency was associated with both severity of COVID and threefold higher odds of mortality. This association was confirmed by another recent review supporting a twofold increased risk of mortality and a fourfold increased risk of critical care admission, although the authors pointed out the weak quality of observational studies.…”
Section: Effects Of Vitamin D Dosing On Acute Respiratory Infections and Coronavirus Disease 2019mentioning
confidence: 99%
“…], not even in rickets, the hallmark condition of severe vitamin D deficiency [12]. This is explained by the induction of the major catabolizing enzyme 24hydroxylase at least for 28 days after a bolus dose.…”
Section: Andandmentioning
confidence: 99%
“…This must be followed by a maintenance dose. Accumulating evidence suggests that bolus doses are, therefore, not suited to improve clinical outcomes in vitamin D-deficient patients [11 ▪▪ ], not even in rickets, the hallmark condition of severe vitamin D deficiency [12]. This is explained by the induction of the major catabolizing enzyme 24-hydroxylase at least for 28 days after a bolus dose.…”
Section: Where Are We Now?mentioning
confidence: 99%